If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 9) + (3x + -12) + 2x = 180 Reorder the terms: (9 + 4x) + (3x + -12) + 2x = 180 Remove parenthesis around (9 + 4x) 9 + 4x + (3x + -12) + 2x = 180 Reorder the terms: 9 + 4x + (-12 + 3x) + 2x = 180 Remove parenthesis around (-12 + 3x) 9 + 4x + -12 + 3x + 2x = 180 Reorder the terms: 9 + -12 + 4x + 3x + 2x = 180 Combine like terms: 9 + -12 = -3 -3 + 4x + 3x + 2x = 180 Combine like terms: 4x + 3x = 7x -3 + 7x + 2x = 180 Combine like terms: 7x + 2x = 9x -3 + 9x = 180 Solving -3 + 9x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 9x = 180 + 3 Combine like terms: -3 + 3 = 0 0 + 9x = 180 + 3 9x = 180 + 3 Combine like terms: 180 + 3 = 183 9x = 183 Divide each side by '9'. x = 20.33333333 Simplifying x = 20.33333333
| 3k-12=2k+10 | | 46x-14x^2-12=0 | | 2(q)+5(1-q)=6q+1(1-q) | | 2p-17=2(p-3)+9 | | 3x^2+22x+40=0 | | 6(5-4x)=-18 | | -7x^2+14x=x | | x(x)+4x=32 | | -3(3+5x)=96 | | 4x^2+4x+1=5 | | -7x^2+14x=y | | 0.18(y-7)+0.04y=0.12y-1.4 | | 4(p)+3(1-p)=3p+7(1-p) | | 0.5v+4.3=2.3 | | -2x-2x-5=5x-2+6 | | 3x^2+12x=y | | (x+4)=5+(5+40) | | v^2+6.1v-6=0 | | 5(4-7x)=405 | | x^2+5x=y | | 9x-4=4x-29 | | 5(p)+6(1-p)=8(p)+3(1-p) | | x-5x+5=13 | | 6(5x+9)=-96 | | 5/7=u/8 | | 25p-12= | | 5(p)+2(1-p)=4(p)+7(1-p) | | -3(y+9)=36 | | -9a^6c^4(5c^3+3a-6)= | | v/9=11/5 | | 2b^2-13b+6=0 | | -4y-y-6=14 |